Author Correction: Solar superstorm of AD 774 recorded subannually by Arctic tree rings - J. Uusitalo (Nature Portfolio, 2019)
The authors became aware of a mistake in the data displayed in Fig. 1 and Supplementary Table 2 of the original version of the Article. Specifically, the 14C production values were printed out in the code before the conversion between the omnidirectional fluence and the flux. As a consequence, the values of the 14C production in Fig. 1 and Supplementary Table 2 were too high by a factor of 4×π = 12.566.. As a result of this, a number of changes have been made to both the PDF and the HTML versions of the Article. A full list of these changes is available online.